2015
DOI: 10.1063/1.4931918
|View full text |Cite
|
Sign up to set email alerts
|

Electron momentum spectroscopy of dimethyl ether taking account of nuclear dynamics in the electronic ground state

Abstract: The influence of nuclear dynamics in the electronic ground state on the (e,2e) momentum profiles of dimethyl ether has been analyzed using the harmonic analytical quantum mechanical and Born-Oppenheimer molecular dynamics approaches. In spite of fundamental methodological differences, results obtained with both approaches consistently demonstrate that molecular vibrations in the electronic ground state have a most appreciable influence on the momentum profiles associated to the 2b1, 6a1, 4b2, and 1a2 orbitals.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 89 publications
4
18
0
Order By: Relevance
“…Comparisons between experiment and theory has shown that taking into account vibrational effects lead to appreciable enhancement of the low p component of the 7t 2 , {2t 1 +3e} and {5t 2 +5a 1 } momentum profiles and considerably improve the agreement with experiment. Further analysis based on the HAQM approach has revealed the significant role of vibrational modes associated with the CH bonds, in line with previous results on molecules with several CH bonds 30,[34][35][36]38 in their contribution to the change of momentum profiles.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Comparisons between experiment and theory has shown that taking into account vibrational effects lead to appreciable enhancement of the low p component of the 7t 2 , {2t 1 +3e} and {5t 2 +5a 1 } momentum profiles and considerably improve the agreement with experiment. Further analysis based on the HAQM approach has revealed the significant role of vibrational modes associated with the CH bonds, in line with previous results on molecules with several CH bonds 30,[34][35][36]38 in their contribution to the change of momentum profiles.…”
Section: Discussionsupporting
confidence: 87%
“…For the {2t 1 +3e} orbitals, the CH wag mode also gives a noticeable contribution to the associated momentum profile at the low p region. The results indicate that taking into account contributions from the normal modes associated with CH bonds is essential for understanding the observed increase in intensity of the 7t 2 and {2t 1 +3e} momentum profiles at small p, being consistent with previous results on ethylene, 30 CH 2 F 2 , 34 furan, 35 dimethyl ether, 36 and oxetane 38 in their contributions to the change of momentum profiles.…”
Section: Contributions From Individual Vibrational Modessupporting
confidence: 90%
See 1 more Smart Citation
“…It was calculated according to the method employed in our previous study. 19 Briefly, a normal mode analysis was carried out using DFT along with the B3LYP functional and aug-cc-pVTZ basis. The KS orbitals were subsequently computed at several nuclear geometries distorted from the equilibrium along each normal coordinate and converted to ρ α (p,Q)'s by means of the HEMS program, assuming constant spectroscopic factors for all orbitals considered.…”
Section: ■ Theoretical Calculationsmentioning
confidence: 99%
“…This molecule has already been the subject of detailed EMS studies at room temperature, 16−19 and appreciable vibrational effects have been identified so far in the electron momentum profiles. 19 It is natural to expect that a larger influence of the nuclear dynamics to the molecular orbitals arises from vibrational excitation, which can easily be induced by heating the sample as dimethyl ether has low-frequency vibrational modes. EMS measurements have thus been performed at a high temperature, 980 K, using a radiative heating system developed in our laboratory.…”
Section: ■ Introductionmentioning
confidence: 99%